Addition of the By-Pass Fat into Diet of Awasi Sheep on Milk Composition - Senyuz, HH; Gümüş, AE (Journal of the Hellenic Veterinary Medical Society, 2024)
By-pass fat is an important source of essential fatty acids for ruminants. It affects yield rather than maintenance requirements. This study was carried out to investigate the effect of adding by-pass fat into diet of dairy sheep on milk components. The study was carried out in a private dairy sheep farm in Konya. For this purpose, 99 Awassi sheep were used after 1 month of the birth during the fresh lactation period. The sheep were randomly divided into 2 groups, the control (C) group (n=54) was fed with total mixed ration (TMR) twice a day, the by-pass fat (BF) group (n=45) was fed with TMR twice a day and 30 g/day of commercial Ca-soap palm oil by-pass fat was given individually during milking. The trial last 15 days with 11 days of adaptation and 4 days of sample collection. The animals in the experimental group consumed 30 g/day of Ca-soap by-pass fat individually during morning milking. The animals were milked for once with an automatic milking system and the lambs were suckled for once by creep. Milk yields of the animals were recorded automatically during the sample collection period, also 50 ml milk samples were taken from each animal at the milking times on the 2nd and 3rd days, and milk fat, non-fat dry matter, protein, lactose, density, freezing point, and somatic cell counts were determined. Fat, non fatty dry matter, density, protein, lactose and somatic cell were respectively; 4.50±0.14 and 5.65±0.17%, 10.86±0.07 and 11.16±0.12%, 34.66±0.45 and 34.33±0.64%, 5.42±0.06 and 5.70±0.10%, 4.49±0.01 and 4.47±0.01%, 121.556±16987 and 171.222±28348 in the C and BF groups, Among milk components, while fat, nonfat dry matter and protein were higher in BF group than C group (p<0.05), density, lactose and somatic cell were similar between groups (p>0.05). It can be concluded that the even though addition of 30 g of Ca soap by-pass fat significantly improved milk fat, non-fat dry matter and protein in dairy sheep fed with TMR at the level of maintenance and yield.